The contribution of economic intelligence to the firm performance - Ben Hadj Hassine, Amine (Yayasan Ahmar Cendekia Indonesia, 2021)
To the extent that the company is an â€œopen systemâ€, it must be in a continuous standby state. In this research work, we will try to focus on the contribution of economic intelligence strategies to the performance of the company. We will begin with a literature review to better understand the theoretical concepts. Then we will conduct a field study of 92 Tunisian industrial companies. Our work has revealed that economic intelligence has a positive but differential effect on the firmâ€™s performance. But some determinants of performance do not seem to take full advantage of the strategies of economic intelligence to which companies should attach greater importance.